Childhood Trauma in Persons With Schizophrenia and a History of Interpersonal Violence - Storvestre, Guttorm Breivik; Jensen, Arvid; Bjerke, Espen; Tesli, Natalia; Rosaeg, Cato; Friestad, Christine; Andreassen, Ole Andreas; Melle, Ingrid; Haukvik, Unn Kristin (Frontiers in Psychiatry, 2020)
Background: Childhood trauma is a risk factor for psychosis as well for violent behavior and -offending later in life. Childhood trauma comprises subdomains of abuse and neglect that may be differently related to later violence among patients with schizophrenia. The aim of this study was to map the subdomains of childhood trauma associated with violent offending in schizophrenia. Methods: Information on childhood trauma from predominantly male patients with a DSM-IV diagnosis of schizophrenia and a history of violent offending (interpersonal violence) (SCZ-V, n=19), schizophrenia patients without a history of violence (SCZ-NV, n=34) and healthy controls (HC, n=66), was obtained with the Childhood Trauma Questionnaire (CTQ). Differences between groups in total maltreatment scores and the five subdomains including physical, emotional, and sexual abuse as well as physical and emotional neglect were analyzed. Results: SCZ-V had the highest median CTQ scores for all sub-domains. SCZ-V reported significantly higher total CTQ scores than SCZ-NV and HC. SCZ-V had significantly higher scores than HC on all subdomains, and significantly higher than SCZ-NV on physical and emotional neglect. SCZ-NV had higher scores on all domains except sexual abuse compared to HC. Conclusion: SCZ-V patients had higher exposure to childhood trauma than SCZ-NV, and both schizophrenia groups had higher exposure than HC. The results suggest that childhood physical- and emotional neglect may be of specific importance to later violence in schizophrenia.